Is the Event Study Methodology Useful for Merger Analysis? A Comparison of Stock Market and Accounting Data - Tomaso Duso; Klaus Gugler; Burcin B. Yurtoglu (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
Using a sample of 167 mergers during the period 1990-2002 involving 544 firms either as merging firms or competitors, we contrast a measure of the merger's profitability based on event studies with one based on accounting data. We find positive and significant correlations between them when using a long window around the announcement date and, for rivals, in case of anticompetitive mergers.
urn:nbn:de:bvb:19-epub-13388-4
Keywords: L4; K21; G34; 330; Mergers; Merger Control; Event Studies; Ex-post Evaluation